2020
DOI: 10.1038/s41583-020-0315-1
|View full text |Cite
|
Sign up to set email alerts
|

The human motor cortex microcircuit: insights for neurodegenerative disease

Abstract: The human motor cortex is selectively vulnerable in a number of neurodegenerative diseases. In this review McColgan et al. integrate layer-specific physiology and pathobiology in the motor cortex thereby generating hypotheses that can be tested in humans using ultra-high resolution neuroimaging techniques. Glossary Anti-sense oligonucleotide therapies-These are single stranded DNA molecules, which bind to target pre-mRNA and recruit RNAse H causing degradation of the complex. This approach has already been app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 181 publications
0
60
0
Order By: Relevance
“…The classical pathophysiological model of PD and recent updates have been established based on experimental and clinical studies (138)(139)(140)(141), which consists of functional disabilities of two main pathways: an "indirect circuit, " which interconnects neocortex-putamen-external pallidum/subthalamic nucleus-SN, and a "direct circuit, " which interconnects neocortex-putameninternal pallidum-SN-thalamus-neocortex. Under the conditions of PD, the reduced dopamine (results from neuronal loss in the SN) inhibits the indirect pathway, resulting in slow movement, and excites the direct pathway that may lead to unwanted movement such as resting tremor.…”
Section: Dti Changes In Dopaminergic Tractsmentioning
confidence: 99%
“…The classical pathophysiological model of PD and recent updates have been established based on experimental and clinical studies (138)(139)(140)(141), which consists of functional disabilities of two main pathways: an "indirect circuit, " which interconnects neocortex-putamen-external pallidum/subthalamic nucleus-SN, and a "direct circuit, " which interconnects neocortex-putameninternal pallidum-SN-thalamus-neocortex. Under the conditions of PD, the reduced dopamine (results from neuronal loss in the SN) inhibits the indirect pathway, resulting in slow movement, and excites the direct pathway that may lead to unwanted movement such as resting tremor.…”
Section: Dti Changes In Dopaminergic Tractsmentioning
confidence: 99%
“…IT neurons preferentially target both ipsilateral striatum and contralateral striatum as well as the cortex. Therefore, IT neurons include both corticostriatal and corticocortical projections, whereas PT neurons preferentially connect brainstem, spinal cord, and ipsilateral striatum (McColgan et al, 2020). In addition, it has been suggested that IT neurons express D 1 receptors and preferentially target dSPNs, whereas PT neurons express D 2 receptors and preferentially connect iSPN in the striatum (Shepherd, 2013), but this hypothesis is challenged by other studies; it has shown that IT and PT neurons project to both iSPN and dSPN in the striatum (Kress et al, 2013).…”
Section: Motor Cortexmentioning
confidence: 99%
“…On a more technical viewpoint, due to the current significant disparity between dMRI voxel dimensions and cellular structures, there is a limited appraisal of the profound microcircuit changes within the GM and its architectural alterations (McColgan et al, 2020). The application of current diffusion models in medicine or biology has raised many questions ins the scientific community (Calamante, 2019;Little and Holloway, 2007).…”
Section: Diffusion Mri: Limitations and Future Directions In Neuroplamentioning
confidence: 99%